Spatio-Temporal Characteristic Analysis of Marine Heatwaves in the Savu Sea (1982-2021) - Rizal Attaqwa; Deodato Naresvara Rayi Respati; Dian Juviani; Sinta Dwis Susilodewi; Laurentia Alexandra Saragih; Ikhsan Mustaqim; Anindya Wirasatriya; Dwi Haryo Ismunarti (Buletin Oseanografi Marina, 2025)
Atmospheric interactions have led to a consistent rise in ocean temperatures in the Indonesian seas, exacerbated by the emergence of marine heatwaves (MHWs) that extend over thousands of kilometers. MHWs are defined as temperature anomalies above the 90th percentile of the sea surface temperature (SST) baseline for at least five consecutive days. The Savu Sea, influenced by the Indonesian throughflow that transports warm water from the Pacific to the Indian Ocean, experiences significant temperature anomalies. This study employs OSTIA L4 Marine Copernicus Global Ocean Physics Reanalysis SST data from 1982 to 2021 to analyze the frequency, duration, and intensity of MHW events in this region. Using Hobday's hierarchical approach, the study finds that MHWs in the Savu Sea lasted up to 1,170 days over 40 years, with 117 recorded events. The worst MHW event occurred in 2016, lasting 194 days with a maximum cumulative intensity of 2.0°C/year, particularly affecting the northern Savu Sea. These heatwaves significantly impact marine ecosystems, leading to coral bleaching that affects about 50% of coral colonies and threatens marine biodiversity and fisheries recovery.